The art of strategy : a game theorist's guide to success in business & life - Dixit, Avinash K.; Nalebuff, Barry (New York : W.W. Norton & Company, 2008)
The book helps to develop ways of thinking about strategic situations that face one on daily basis using the game theory.
Includes bibliographical references (p. 457-472) and index.
nif 23/04/13
Loans
Keywords: Strategic planning; Strategy; Game theory; Decision making